Shifting representations of the Samsui women and the Amahs from the 1980s to 1990s : through the media - Lum, Xin Yi (Nanyang Technological University, 2022)
As characteristics of hard work and resilience dominated the popular discourse of the Samsui women and the Amahs, this effectively reduced them to labourers of the early development of Singapore. Hence, this paper seeks to expand on this discourse by shedding light on the shifting representations of these two groups of women through the lens of the media from the 1980s to the 1990s. Through the analysis of state-directed media pieces and socio-political policies of that period, this paper highlights how the policies underlie the media portrayals of these women. As such, this paper argues that from the 1980s to 1990s, portrayals of the Samsui women and the Amahs were reconstructed and aligned to the state’s social engineering initiatives that underpinned the goals of maintaining the normative family unit and encouraging loyalty to the nation.